Targeting multiple signaling pathways: the new approach to acute myeloid leukemia therapy - Jenna L. Carter; Katie Hege; Jay Yang; Hasini A. Kalpage; Yongwei Su; Holly Edwards; Maik Hüttemann; Jeffrey W. Taub; Yubin Ge (2020)
Abstract Acute myeloid leukemia (AML) is the most common form of acute leukemia in adults and the second most common form of acute leukemia in children. Despite this, very little improvement in survival rates has been achieved over the past few decades. This is partially due to the heterogeneity of AML and the need for more targeted therapeutics than the traditional cytotoxic chemotherapies that have been a mainstay in therapy for the past 50 years. In the past 20 years, research has been diversifying the approach to treating AML by investigating molecular pathways uniquely relevant to AML cell proliferation and survival. Here we review the development of novel therapeutics in targeting apoptosis, receptor tyrosine kinase (RTK) signaling, hedgehog (HH) pathway, mitochondrial function, DNA repair, and c-Myc signaling. There has been an impressive effort into better understanding the diversity of AML cell characteristics and here we highlight important preclinical studies that have supported therapeutic development and continue to promote new ways to target AML cells. In addition, we describe clinical investigations that have led to FDA approval of new targeted AML therapies and ongoing clinical trials of novel therapies targeting AML survival pathways. We also describe the complexity of targeting leukemia stem cells (LSCs) as an approach to addressing relapse and remission in AML and targetable pathways that are unique to LSC survival. This comprehensive review details what we currently understand about the signaling pathways that support AML cell survival and the exceptional ways in which we disrupt them.